2017
DOI: 10.1364/oe.25.020737
|View full text |Cite
|
Sign up to set email alerts
|

Polarization squeezing at the audio frequency band for the Rubidium D_1 line

Abstract: A 2.8-dB polarization squeezing of the Stokes operatorS^for the rubidium D line (795 nm) is achieved, with the lowest squeezing band at an audio frequency of 2.6 kHz. It is synthetized by a bright coherent beam and a squeezed vacuum, which are orthogonally polarized and share same frequency. Two methods are applied to support the optical parametric oscillator: an orthogonally-polarized locking beam that precludes residual unwanted interference and quantum noise locking method that locks the squeezing phase. Be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…At the analysis frequency of 2 MHz, we have prepared 795-nm SVS with squeezing level of -5.6 dB [18]. However, the preparation of PSS at the audio-frequency is relatively difficult due to the challenging control of system noise and the serious coupling of ambient noise [19,24], we have demonstrated that the squeezing level of PSS can be improved experimentally by using the laser intensity noise suppression systems based on acousto-optic modulator [25]. In this work, SVS with squeezing level of -4.0±0.3 dB (the blue dash line) and anti-squeezing level of +7.0±0.3 dB (the pink dash line) can be obtained at the analysis frequency of 10 kHz by scanning the LO beam's phase, as shown by the red curve in figure 3 (a); PSS with relative noise power in S 2 is ∼ -3.7±0.3 dB (the noise level is about 0.43 times of SNL), as shown by the red line in figure 3 (b).…”
Section: Methodsmentioning
confidence: 99%
“…At the analysis frequency of 2 MHz, we have prepared 795-nm SVS with squeezing level of -5.6 dB [18]. However, the preparation of PSS at the audio-frequency is relatively difficult due to the challenging control of system noise and the serious coupling of ambient noise [19,24], we have demonstrated that the squeezing level of PSS can be improved experimentally by using the laser intensity noise suppression systems based on acousto-optic modulator [25]. In this work, SVS with squeezing level of -4.0±0.3 dB (the blue dash line) and anti-squeezing level of +7.0±0.3 dB (the pink dash line) can be obtained at the analysis frequency of 10 kHz by scanning the LO beam's phase, as shown by the red curve in figure 3 (a); PSS with relative noise power in S 2 is ∼ -3.7±0.3 dB (the noise level is about 0.43 times of SNL), as shown by the red line in figure 3 (b).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, the use of PSS of light can still improve the SNR of SNS without changing the FWHM. Typically, when the transverse magnetic field is 34.6 µ T, the corresponding Larmor precession frequency of 85 Rb is about 163 kHz, and the squeezing level of PSS we use is only -3.7 dB due to the coupling of various noises at this analytical frequency [26,27]. In order to effectively protect the quantum properties of PSS of light after passing through the atomic vapor cell and to ensure that paraffin film on the inner wall is not damaged [28], the temperature of cell we chose is 45 ℃.…”
Section: Quantum Enhanced Spin Noise Spectroscopymentioning
confidence: 99%
“…All the abovementioned schemes are used for various applications which cover the laser writing system 27 , coherent population trapping clock 28 , and other optical devices 29 . Here, we aim to reduce the laser intensity noise to weaken its negative impact on preparation and detection of squeezed light at audio frequency range 30,31 .…”
Section: Introductionmentioning
confidence: 99%